Gastroenterology in Rodents - Jekl, Vladimír; Modry, David (The veterinary clinics of North America. Exotic animal practice, 2025)
Gastrointestinal (GI) diseases are frequently diagnosed in rodents. Clinical signs are usually nonspecific and include anorexia, weight loss, chronic wasting, abdominal discomfort, gas accumulation in the intestine and stomach, and diarrhea. Malabsorption associated with GI dysfunction or gastroenteritis quickly leads to negative energy balance and metabolic acidosis. Therefore, all disorders of the GI tract should be treated as soon as possible. The article describes selected disorders of the GI tract in guinea pigs (Cavia porcellus), chinchillas (Chinchilla lanigera), degus (Octodon degus), and rats (Rattus norvegicus).
Keywords: Degu; Rodentia; Hamster; morčata; Rats; Chinchilla; gastrointestinální nemoci; hlodavci; Rodent Diseases; Rat; Animals; Gastrointestinal Diseases; Gastrointestinal disease; nemoci hlodavců; Gastric dilatation and volvulus; Guinea pig; zvířata; Enteritis; krysa rodu Rattus; Guinea Pigs